Problems in Information Transfer in India - Ramaseshan, S. (Journal of Information and Knowledge, 1978)
Traces the possible causes for the "information explosion". Emphasizes the need for assessing quality of scientific reporting and publication;and highlights the problems of scientific and technology information transfer in India.